CHARACTERISTICS OF JOHN DEWY'S PROJECT TECHNOLOGY IN PERSONAL FORMATION IN MODERN EDUCATION - Shukurov Nusratillo Narzullaevich; Supiev Shavkat Akhmatovich (Journals Park Publishing, 2022)
In this article, at the beginning of the 20th century, the well-known pedagogue John Dewey and his follower U. X. Project technology created by Kilpatrick, its content - essence, main concepts, its types, stages of using Project technology and project annotation created for the purpose of using this technology are covered.
Keywords: Project technology, pedagogy, class, lesson, learner, school, teaching, work, game, student